The role of reaction conditions in the polymorphic control of Eu3+ doped YInO3: structure and size sensitive luminescence. Issue 23 (23rd December 2014) - Shukla, R.; Gupta, Santosh K.; Grover, V.; Natarajan, V.; Tyagi, A. K.
Abstract : Controlled synthetic conditions yielded YInO3 :Eu 3+ in both C-type and hexagonal modifications which exhibited a tremendous bearing of size and local structure on Eu 3+ luminescence, all in a single compound. Abstract : With the aim of exploring the effect of particle size and different polymorphic structures on the luminescence behaviour of Eu 3+ ions, all in a single compound, the YInO3 :Eu 3+ system was synthesized. Metastable C-type modification could be obtained in YInO3 nanopowders synthesized by gel combustion. The broadening in Raman modes has been related to both the particle size and the strain in the metastable C-type modification. The hexagonal polymorph of YInO3, with a layered structure, quite unlike the C-type modification, could be obtained by heating nanopowders to 1175 °C. Such a change in the structure, leading to different site symmetries for Eu 3+ ions exhibited a tremendous bearing on its luminescence behaviour. Detailed steady state and time resolved luminescence studies revealed a highly distorted local site symmetry for the Y 3+ ion in hexagonal YInO3 . The nano C-type YInO3 exhibited greater asymmetry and a shorter lifetime as compared to the bulk C-type YInO3, attributable to more surface defects in the case of the former. The Judd–Ofelt parameters ( Ω 2 and Ω 4 ) were determined which established a much higher asymmetry in the hexagonal modification. Along with higher lifetime, the hexagonal polymorph also possessed superior quantum yield values. In addition to providing a significant insight into the structure–luminescence correlation in this study, we propose an efficient red phosphor with a high red color purity.